(untitled) (Al-Muthanna Journal of Sport Education Sciences, 2026)
This study aimed to construction of two tests for coordination abilities and to determine their predictive power regarding the effectiveness of receiving and serving skills among female volleyball players. The researchers adopted a descriptive approach with a correlational method, as it was suitable for the nature of the research problem. The research population consisted of club players in the Iraqi Women’s Premier Volleyball Championship (2024), and the research sample comprised 146 players. Two tests were developed: the overhead passing test with the arms between the sticks and the motor response test for receiving shots hit on a Swiss ball. Both tests demonstrated acceptable scientific coefficients. The research results showed the possibility of generating standardized score tables and levels for the two developed tests. The researchers developed an equation for predicting the effectiveness of blocking skills using the Click & Scout analytical program, based on the factors used to construct the two tests. The results of the linear regression method showed that the motor response test for receiving shots hit on a Swiss ball was more effective in predicting the effectiveness of receiving and serving skills among female volleyball players, reaching a statistically significant level. While the overhead arm-to-arm passing test between the sticks proved less effective in predicting the effectiveness of volleyball players’ serve-receiver performance, it did not reach statistical significance. The researchers recommended future research to develop tests measuring coordination abilities and linking them to offensive and defensive skills across different age groups and skill levels.